A Survey of Communications and Collaborative Web Technologies - Narayanan, Kulathuramaiyer; Hermann, Maurer (International Journal of Computer and Information Technology (IJCIT), 2015)
The web has changed the way we do things in a variety of ways. It is not uncommon to associate the term disruptive technologies to the radical changes happening on the web. This paper takes an encompassing view of developments surrounding the web with a particular emphasis on emerging trends and evolving application scenarios. We provide a broad overview of technologies, in revealing directions for emerging developments as well as directions for next-generation developments. This survey paper first reviews aspects of the web growth and its contributing factors such as the expanding landscape of social networks, mass collaborative system capabilities, and eCommunities. We then present concerns relating to the numerous developments, particularly with respect to social and political developments. This paper clearly points out the knowledge gaps and the ensuing dangers arising from the purely commercial perspectives and motivation that is driving the web. By focusing on the trees rather than the forest as a whole, we are in the process of losing ourselves and endangering our future. Subsequently, we explore the implications of current developments in enabling the web to serve as a platform for serious work, in allowing users to focus on creatively shaping of our world.